Use of Quranotherapy among patients with Epilepsy - ÇAKSEN, HÜSEYIN (Pakistan Journal of Medical & Health Sciences, 2025)
Millions of people worldwide live with epilepsy and need long-term medication. Recently, the use of complementary and alternative medicine (CAM) has increased in epilepsy. Approximately half of epilepsy patients use at least one CAM. Mind-body medicine incorporates a practices that take advantage of the interactions among the mind, brain, body, and behavior to affect body functions. Mind-body practices use the mind to affect physical functioning and promote health. Mind-body medicine such as meditation, mindfulness, cognitive behavioral therapy, biofeedback, music, yoga, etc., is one of the most common used of CAMs for treatment of epilepsy. The Quran is the instructor, true wisdom, guide, and leader of the world of humanity; it is both a book of wisdom and law, a book of prayer and worship, a book of command and summons, and a book of invocation and Divine knowledge – it is a book for all spiritual needs; and it is a sacred library offering books appropriate to the ways of all the saints and veracious, the purified and the scholars, whose ways and paths are all different1. The Quranotherapy (or Quranic therapy), a modality of transcendental meditation, involves reciting, reading and listening to the Quran to improve physical, social, mental, spiritual and/or religious health. Herein, we discussed use of the Quran as a cure and remedy in patients with epilepsy to emphasize that the Quranotherapy is a meditation modality. Meditation and religious therapies are commonly used in patients with epilepsy in many cultures around the world. In the series of McConnell et al2, overall CAM use was 70%, with the use of prayer/spirituality in 31% and meditation in 19%. Of the patients, 44% reported improved seizure control with CAM. Stress management accounted for perceived seizure reduction in 74%, followed by marijuana (54%), prayer (49%), and yoga (42%)2. Asadi-Pooya et al3 found that 72.3% of physicians believed that CAM might be helpful in patients with epilepsy. They also noted that 22.3% of participants used/prescribed CAM to patients with epilepsy; among them, 46.5% of people found CAM to be safer than conventional antiseizure medications. The most common endorsed CAM included meditation (41%), and the ratio of prayers was 15%3. Al-Rumayyan et al4 reported that the prevalence of CAM usage was 42% among pediatric neurology patients (40% of patients had epilepsy), and the most common (66%) type of CAM was the Quranotherapy. In another series, 56% of parents had used CAM for their child’s neurological illness (28% of patients had epilepsy). The most common modality (77%) was prayer/ Quranotherapy5. Two most popular therapeutic modalities were drug treatment alone (85.3%) and associated with the Quranotherapy (35.3%) among people with epilepsy6. Quranotherapy has been commonly used among patients with epilepsy and their caregivers and most of them believed that Quranotherapy helped in coping with epilepsy7-10. Quranotherapy was constantly used by all the participants with epilepsy in the study of Kissani et al9 In another series, 90% patients with epilepsy believed that Quranotherapy helped in coping with epilepsy10. In a large series, 31.5% of individuals among general population believed that epilepsy could be treated by the Quranotherapy11. Hijazeen et al12 noted that the most common (71.4%) reported treatment method in epilepsy was the Quranotherapy among university students. In another study, 34.6% of medical students thought the Quranotherapy was an appropriate treatment for epilepsy13. In conclusion, we would like to emphasize that the Quranotherapy is one of the meditation modalities. Secondly, Quranotherapy has been frequently used among patients with epilepsy and their caregivers for treatment of epilepsy in many parts of the world because they believe the following ayat of the Quran: “We send down (stage by stage) in the Quran that which is a shifa (healing) and a mercy to those who believe14. Based on the interpretation of shifa from mufassirun (interpreters), the outline of shifa concept is as follows: (a) Allah has absolute authority to spread and shifa all diseases to mankind; (b) The Quran is a divine revelation from Allah as shifa for human disease, especially spiritual disease; (c) Allah had created natural resources as medication for physical disease15. Thirdly, further studies using neurobiochemical and neurohormonal analyses and electrophysiological and neuroimaging techniques should be conducted to determine how effective Quranotherapy is in patients with epilepsy. Finally, we recommend that randomized controlled studies should be conducted about use of the Quranotherapy in epileptic patients in societies with different cultures and religious beliefs.